Aromatherapy with ylang ylang for anxiety and self-esteem: a pilot study - Juliana Rizzo Gnatta; Patricia Petrone Piason; Cristiane de Lion Botero Couto Lopes; Noemi Marisa Brunet Rogenski; Maria Júlia Paes da Silva (SciELO, 2014)
Objective: To verify if the use of ylang ylang essential oil by cutaneous application or inhalation alters the anxiety and self-esteem perception and physiological parameters as blood pressure and temperature. Method : A pilot study with 34 professionals from a nursing group randomized in three groups: one received the ylang ylang essential oil by cutaneous application, the second received through inhalation and the third (placebo) received the ylang ylang essence through cutaneous application. The assessment was done by an Anxiety Inventory (IDATE) and the Dela Coleta self-esteem scale, applied on baseline, after 30, 60 and 90 days and after 15 days post-intervention (follow up). Results : In the pre and post-intervention intergroup analysis, there was a significant difference in self-esteem for the three groups (p values: G1=0.014; G2=0.016; G3=0.038). There were no differences in the analysis between groups for anxiety or for physiological parameters. Conclusion : It was found significant alterations only to the intergroup perception of self-esteem for the three groups.